2017
DOI: 10.1002/2016gc006604
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy in the lowermost mantle beneath the Indian Ocean Geoid Low from ScS splitting measurements

Abstract: The Indian Ocean Geoid Low (IOGL) to the south of Indian subcontinent is the world's largest geoid anomaly. In this study, we investigate the seismic anisotropy of the lowermost mantle beneath the IOGL by analyzing splitting of high‐quality ScS phases corrected for source and receiver side upper mantle anisotropy. Results reveal significant anisotropy ( ∼1.01%) in the D′′ layer. The observed fast axis polarization azimuths in the ray coordinate system indicate a TTI (transverse isotropy with a tilted axis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 115 publications
(128 reference statements)
2
5
0
Order By: Relevance
“…Our findings affirm the existence of hot material at the depths of MTZ. These results and the observations from previous studies beneath the study region prompt us to interpret that 10.1029/2020GC009079 the world's largest geoid anomaly could be explained by the combined effect of (i) high-velocity/density anomalies in the lowermost mantle associated with slab graveyards (Rao & Kumar, 2014;Rao et al, 2017) and (ii) the low-velocity/density material in the mid mantle (present study) sourced from the African LLSVP. The interpretation supports the outcome of geodynamical modeling (Spasojevic et al, 2010), which advocates that the slab graveyards at the CMB alone cannot explain the long-wavelength geoid anomaly, necessitating the existence of a low-velocity/density anomaly at mid-to-upper mantle depths.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Our findings affirm the existence of hot material at the depths of MTZ. These results and the observations from previous studies beneath the study region prompt us to interpret that 10.1029/2020GC009079 the world's largest geoid anomaly could be explained by the combined effect of (i) high-velocity/density anomalies in the lowermost mantle associated with slab graveyards (Rao & Kumar, 2014;Rao et al, 2017) and (ii) the low-velocity/density material in the mid mantle (present study) sourced from the African LLSVP. The interpretation supports the outcome of geodynamical modeling (Spasojevic et al, 2010), which advocates that the slab graveyards at the CMB alone cannot explain the long-wavelength geoid anomaly, necessitating the existence of a low-velocity/density anomaly at mid-to-upper mantle depths.…”
Section: Discussionsupporting
confidence: 84%
“…The present study vindicates the presence of hot anomalies at the mid mantle depths beneath this region. Therefore, the origin of the world's largest geoid anomaly, that is, IOGL, could be due to a combined effect of (i) high-velocity anomalies in the lowermost mantle due to slab graveyards (Rao & Kumar, 2014;Rao et al, 2017) and (ii) lowvelocities/densities in the mid mantle due to hot materials sourced from the African Large Low Shear Velocity Province (LLSVP) (Grand, 2002;Masters et al, 2000;Montelli et al, 2006;Ritsema et al, 2004Ritsema et al, , 2011Simmons et al, 2007Simmons et al, , 2010Su & Dziewonski, 1997), as also evidenced by the results from the present study.…”
Section: 1029/2020gc009079supporting
confidence: 71%
See 2 more Smart Citations
“…The Tethyan slab has been subducting to the lowermost mantle since the late Jurassic (~150 Ma; Van der Voo et al, 1999), and its seismic signature has been reported by several studies. For example, Rao et al (2017) found substantial anisotropy in the lowermost mantle beneath the Indian Ocean from ScS splitting measurements, which they attributed to lattice preferred orientation deformation of the Tethyan subducted slab dipping southwestwardly. This geometry is consistent with the migration of the subducted Tethyan slab toward the African LLSVP with time, which in turn may have pushed the LLSVP westward.…”
Section: 1029/2020jb019929mentioning
confidence: 99%